2008 30th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2008
DOI: 10.1109/iembs.2008.4649288
|View full text |Cite
|
Sign up to set email alerts
|

Detection of brachytherapy seeds using 3D ultrasound

Abstract: Imaging and detection of brachytherapy seeds using transrectal ultrasound (TRUS) remains a challenge for prostate brachytherapy, mainly due to the small size of brachytherapy seeds in relatively low-quality B-mode TRUS images. In this paper, we propose a new solution for brachytherapy seed detection using 3D ultrasound. We use 3D reflected power images computed from ultrasound radio-frequency signals, instead of using conventional B-mode images. Then implanted seeds are detected in 3D local search spaces that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…A number of studies have also used an industrial prostate phantom commercialized by CIRS (Computerized Imaging Reference Systems, Inc). 15,16 This phantom consists of prostate and seminal vesicles embedded in surrounding tissue and has a perineal surface, along with a rectum and urethra. None of these phantoms were designed to simulate prostate motion.…”
Section: Ib Prior Artmentioning
confidence: 99%
“…A number of studies have also used an industrial prostate phantom commercialized by CIRS (Computerized Imaging Reference Systems, Inc). 15,16 This phantom consists of prostate and seminal vesicles embedded in surrounding tissue and has a perineal surface, along with a rectum and urethra. None of these phantoms were designed to simulate prostate motion.…”
Section: Ib Prior Artmentioning
confidence: 99%
“…The other approach is motion management, rather than mitigation. By detecting the needles and/or seeds in the TRUS images [31]- [33], precise information can be provided to the clinician to help make informed decisions on how to proceed (whether this be needle re-positioning or modification of the planning). This detection also allows for automatic update of the dosimetry for post-operative evaluation.…”
Section: B Robotics In Ldr Prostate Brachytherapymentioning
confidence: 99%
“…To achieve this goal, we have studied the reflected power images extracted from radio frequency ultrasound data for seed detection [8]. We have also shown that the use of reflected power images in combination with template matching techniques can result in detection of needle paths on sagittal ultrasound images [9], and that the use of a priori information, such as knowledge of the plan, may be useful in developing ultrasound-only dosimetry [10].…”
Section: Introductionmentioning
confidence: 99%
“…The measures of visibility are extracted from reflected power (RP) images [10]. We have performed these experiments in preparation for a clinical study to measure the clinical impact of using the EchoStrand in brachytherapy.…”
Section: Introductionmentioning
confidence: 99%